CHARTING RESEARCH TRENDS ON UNIVERSITY AWARENESS AND VOLUNTEERISM: A BIBLIOMETRIC STUDY OF INCLUSIVE EDUCATION FOR PERSONS WITH DISABILITIES - Zulqarnain, Muhammad Amir; Rashid , Syar Meeze Mohd; Yahya, Siti Farisah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
This study maps the global research landscape on university awareness and volunteerism in relation to disability-inclusive higher education for persons with disabilities (PWD). Although previous studies have examined disability awareness, inclusive education and volunteer engagement separately, limited bibliometric evidence has systematically integrated these three areas within a single analytical framework. Existing scholarship also remains geographically uneven, with limited visibility of research from Global South and ASEAN higher education contexts. To address these gaps, this study conducted a bibliometric analysis of Scopus-indexed journal articles published between 2019 and 2024. The analysis employed VOSviewer version 1.6.20 to examine publication trends, country-level co-authorship networks, citation patterns and keyword co-occurrence structures. The findings show that research on PWD awareness and volunteerism in higher education is largely concentrated in high-income Western countries, particularly the United States, United Kingdom, Canada and Australia, while contributions from ASEAN and other Global South regions remain comparatively limited. The results further suggest that post-COVID-19 scholarship has increasingly shifted toward psychosocial support, empowerment and inclusive institutional responsibility. This study contributes theoretically by clarifying the intellectual structure of research linking university awareness, volunteerism and disability-inclusive education. Practically, it provides evidence-based insights for universities, policymakers and disability support practitioners to strengthen inclusive volunteer programmes, institutional awareness strategies and culturally responsive support systems for PWD in higher education.